Enhanced antimicrobial efficacy and energy efficiency of low irradiance 405-nm light for bacterial decontamination - Lucy G. Sinclair; John G. Anderson; Scott J. MacGregor; Michelle Maclean (Archives of Microbiology, 2024)
Due to its increased safety over ultraviolet light, there is interest in the development of antimicrobial violet-blue light technologies for infection control applications. To ensure compatibility with exposed materials and tissue, the light irradiances and dose regimes used must be suitable for the target application. This study investigates the antimicrobial dose responses and germicidal efficiency of 405 nm violet-blue light when applied at a range of irradiance levels, for inactivation of surface-seeded and suspended bacteria. Bacteria were seeded onto agar surfaces (10 1 –10 8 CFUplate −1 ) or suspended in PBS (10 3 –10 9 CFUmL −1 ) and exposed to increasing doses of 405-nm light (≤ 288 Jcm −2 ) using various irradiances (0.5–150 mWcm −2 ), with susceptibility at equivalent light doses compared. Bacterial reductions ≥ 96% were demonstrated in all cases for lower irradiance (≤ 5 mWcm −2 ) exposures. Comparisons indicated, on a per unit dose basis, that significantly lower doses were required for significant reductions of all species when exposed at lower irradiances: 3–30 Jcm −2 /0.5 mWcm −2 compared to 9–75 Jcm −2 /50 mWcm −2 for low cell density (10 2 CFUplate −1 ) surface exposures and 22.5 Jcm −2 /5 mWcm −2 compared to 67.5 Jcm −2 /150 mWcm −2 for low density (10 3 CFUmL −1 ) liquid exposures (P ≤ 0.05). Similar patterns were observed at higher densities, excluding S. aureus exposed at 10 9 CFUmL −1 , suggesting bacterial density at predictable levels has minimal influence on decontamination efficacy. This study provides fundamental evidence of the greater energy efficacy of 405-nm light for inactivation of clinically-significant pathogens when lower irradiances are employed, further supporting its relevance for practical decontamination applications.

Rapid subsidence in the Kathmandu Valley recorded using Sentinel-1 InSAR - Jingqiu Huang; Hugh Sinclair; Prakash Pokhrel; C. Scott Watson (International Journal of Remote Sensing, 2024)

Downscaling climate projections over large and data sparse regions: Methodological application in the Zambezi River Basin - Nadav Peleg; Scott Sinclair; Simone Fatichi; Paolo Burlando (International Journal of Climatology, 2020)
Climate impact studies often require climate data at a higher space–time resolution than is available from global and regional climate models. Weather generator (WG) models, generally designed for mesoscale applications (e.g., 10 1 –10 5 km 2 ), are popular and widely used tools to downscale climate data to finer resolution. One advantage of using WGs is their ability to generate the necessary climate variables for impact studies in data sparse regions. In this study, we evaluate the ability of a previously established state of the art WG (the AWE‐GEN‐2d model) to perform in data sparse regions that are beyond the mesoscale, using the Zambezi River basin (10 6 km 2 ) in southeast Africa as a case study. The AWE‐GEN‐2d model was calibrated using data from satellite retrievals and climate re‐analysis products in place of the absent observational data. An 8‐km climate ensemble at hourly resolution, covering the period of 1976–2099 (present climate and RCP4.5 emission scenario from 2020), was then simulated. Using the simulated 30‐member ensemble, climate indices for both present and future climates were computed. The high‐resolution climate indices allow detailed analysis of the effects of climate change on different areas within the basin. For example, the southwestern area of the basin is predicted to experience the greatest change due to increased temperature, while the southeastern area was found to be already so hot that is less affected (e.g., the number of 'very hot days' per year increase by 18 and 9 days, respectively). Rainfall intensities are found to increase most in the eastern areas of the basin (1 mm·d −1 ) in comparison to the western region (0.3 mm·d −1 ). As demonstrated in this study, AWE‐GEN‐2d can be calibrated successfully using data from climate reanalysis products in the absence of ground station data and can be applied at larger scales than the mesoscale.

Cranial morphological scaling and relative prey size limitations for a native predator in an invaded system - Eliza I. Gilbert; Scott L. Durst; Angela P. James; Jason E. Davis; Thomas B. Sinclair; Nathan R. Franssen (Environmental Biology of Fishes, 2018)

Recovery following a marathon: a comparison of cold water immersion, whole body cryotherapy and a placebo control - Laura J. Wilson; Emma Cockburn; Katherine Paice; Scott Sinclair; Tanwir Faki; Frank A. Hills; Marcela B. Gondek; Alyssa Wood; Lygeri Dimitriou (European Journal of Applied Physiology, 2018)

Baseline Ecological Risk Assessment of the Calcasieu Estuary, Louisiana: Part 3. An Evaluation of the Risks to Benthic Invertebrates Associated With Exposure to Contaminated Sediments - Donald D. MacDonald; Christopher G. Ingersoll; Nile E. Kemble; Dawn E. Smorong; Jesse A. Sinclair; Rebekka Lindskoog; Gary Gaston; Denise Sanger; R. Scott Carr; James Biedenbach; Ron Gouguet; John Kern; et al. (Archives of Environmental Contamination and Toxicology, 2011)